Pengaruh Simpanan Anggota dan Pembiayaan terhadap SHU pada KSPPS BMT Sinergi Cendekia Indonesia - Herlan Firmansyah; Idris Gosali; Cucu Mukaromi; Wilda Rahmatika; Yana Mulyana (Masoem University, 2022)
The purpose of this study is to describe and analyze the partial and simultaneous influence of member deposits and financing on profit (SHU) on KSPPS BMT Sinergi Cendekia Indonesia. The research approach used is a quantitative approach with descriptive-analytical methods, the data source used is a five-year safe secondary data, the data collection techniques used are library studies and documentation. The data analysis technique used is multiple linear regression analysis. The results showed that partially member deposits did not affect SHU, financing did not affect SHU and simultaneous deposits and financing did not affect SHU. The implication is that the SHU forming component in BMT does not have to be formed from financing activities alone but can be formed from real sector activities and partnerships between BMT as developed by KSPPS BMT Sinergi Cendekia Indonesia.